THE RELATIONSHIP BETWEEN FISCAL RULES AND MACROECONOMIC PERFORMANCE: EMPIRICAL ANALYSIS (Third Sector Social Economic Review, 2021)
Fiscal rules; are permanent limits or limits on public expenditure, tax rates, exemptions and exemptions, reductions, and various fiscal policy indicators such as the public budget and government borrowing. Although its history goes back a long way, today fiscal rules are recommended in order to ensure fiscal discipline and thus positively affect macroeconomic stability. When the pioneering studies on fiscal rules are examined, it is seen that they mostly focus on the conceptual framework of fiscal rules and their effects on fiscal discipline. Considering the empirical studies conducted in the last decade, the opinion that fiscal rules positively affect macroeconomic variables such as price stability and growth comes to the fore. In this study, the effect of fiscal rule practices on budget deficit, inflation rate and growth rates in selected countries was investigated. In this framework, the budget deficit, inflation and growth rates before and after the fiscal rules for the 29-year period, starting from 1988 to 2016, of twenty-four selected countries around the world were examined by Panel Data Analysis. According to the findings obtained from the analysis, fiscal rules both help to ensure fiscal discipline and positively affect price stability, macroeconomic stability and economic growth.
Keywords: Fiscal rules; budget deficit; price stability; growth; panel data analysis.